2008
DOI: 10.1116/1.2968615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of base and photoacid generator on deprotection blur in extreme ultraviolet photoresists and some thoughts on shot noise

Abstract: Extreme ultraviolet lithography based nanofabrication using a bilevel photoresistA contact-hole deprotection blur metric has been used to monitor the deprotection blur of an experimental open platform resist ͑EH27͒ as the wt % of base and photoacid generator ͑PAG͒ were varied. A six times increase in base wt % is shown to reduce the size of successfully patterned 1:1 line-space features from 52 to 39 nm without changing deprotection blur. Corresponding isolated line edge roughness is reduced from 6.9 to 4.1 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…If we simply assume the dose noise to go as the square root of the mean dose, a 25% reduction in noise would require a 56% increase in dose. This arguably represents the "shot noise limit" [8][9][10][11][12][13][14][15][16][17][18][19]], yet we find that by biasing the CD by 2 nm we significantly outperform this "limit". Figure 11 shows the corresponding PDFs for the original case in Fig.…”
Section: Predicting Error Ratesmentioning
confidence: 89%
“…If we simply assume the dose noise to go as the square root of the mean dose, a 25% reduction in noise would require a 56% increase in dose. This arguably represents the "shot noise limit" [8][9][10][11][12][13][14][15][16][17][18][19]], yet we find that by biasing the CD by 2 nm we significantly outperform this "limit". Figure 11 shows the corresponding PDFs for the original case in Fig.…”
Section: Predicting Error Ratesmentioning
confidence: 89%
“…We also include previously reported base loading data for EH27 resist for completeness. 12 Through base, the XP 5435 and XP 5271 platforms experience marginal reductions in deprotection blur while the XP 5496 and EH27 platforms see no statistically significant change in blur. The deprotection blur of XP 5435F is missing because we never exposed contacts for this resist.…”
Section: Metrologymentioning
confidence: 91%
“…Several authors have reported that increased levels of base and photoacid generator ͑PAG͒ in EUV resists lead to improved LER and patterning ability. [10][11][12] In recent work, 12 the contact-hole metric was used to monitor the deprotection blur in an experimental open platform resist ͓EH27 ͑Ref. 13͔͒ as the weight percent of base and PAG were varied.…”
Section: Introductionmentioning
confidence: 99%
“…The solutions given in Eqs (13)(14)(15) are valid for any two times t and t + ∆t with ∆t > 0. Hence we could have used 0 and some total time T instead of t and t + ∆t.The reason for using t and t + ∆t is that the solution approach used here is to iterate between the solutions given in Eqs (13)(14) and in Eq (15) 10 That is, turn off the diffusion (set D acid = D base = 0) and solve for ρ acid and ρ base at time t + ∆t given their values everwhere at time t using Eq (15).…”
Section: Mask Ler and Surface Roughness Effects In Resistmentioning
confidence: 98%